A method for homogenizing the deformed TiAl alloy structure

By employing a step-by-step heat treatment process, the problem of uneven residual lamellar structure in deformed TiAl alloys was solved, resulting in a fine and uniform full lamellar structure. This improved the overall performance of the alloy, making it suitable for lightweighting in aerospace and vehicle engines.

CN116240476BActive Publication Date: 2025-03-04UNIV OF SCI & TECH BEIJING
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211695083.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-03-04
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

Existing technologies are insufficient to effectively eliminate residual lamellar structures in deformed TiAl alloys, resulting in uneven microstructure and affecting the overall performance of the alloy.

Method used

A step-by-step heat treatment process is adopted, including holding in the (α+γ) two-phase region, the middle and upper temperature region, the γ solution region, and cooling near the eutectoid transformation temperature. The cooling rate is controlled to obtain a uniform full lamellar or near-full lamellar structure.

Benefits of technology

By employing a step-by-step heat treatment process, the microstructure of the TiAl alloy was homogenized, resulting in a fine and uniform full-lamellar structure. This improved the overall performance of the alloy and provided an ideal microstructure basis for subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116240476B_ABST
    Figure CN116240476B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for homogenizing and regulating the structure of a deformed TiAl alloy, which belongs to an aluminum-titanium alloy used in the fields of aerospace and automobile manufacturing. The present invention mainly regulates the structure morphology and the size of lamellar groups and lamellar interlamellar of the deformed TiAl alloy. The deformed TiAl alloy is heated from room temperature to the middle and upper temperature zone of the (α+γ) dual-phase region in a heat treatment furnace for 7 to 24 hours, then quickly transferred to a high-temperature furnace at 0 to 50°C above the γ solid solution temperature for 5 to 60 minutes, and then quickly transferred to another high-temperature furnace near the eutectoid transformation temperature for 0 to 60 minutes, and then temperature-controlled cooling is performed to obtain a TiAl alloy with uniform microstructural distribution. The present invention can obtain a full lamellar or nearly full lamellar structure with uniform microstructural distribution and fine size through multi-step heat treatment, and the size of the lamellar group can be controlled at 40 to 100 μm. The method has a short process, a simple process, and strong operability. It does not require quenching treatment to avoid the generation of microcracks, and provides a method for homogenizing the structure of a deformed TiAl alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a TiAl alloy used in the fields of aerospace, vehicles, etc., and more specifically, to a method for homogenizing and controlling the structure of a deformed TiAl alloy. Background Art

[0002] TiAl alloy is a hot research topic for lightweight aerospace in the future due to its advantages of light weight, high strength, excellent high temperature mechanical properties, and outstanding oxidation resistance. The density of TiAl alloy is half of the current high temperature alloy, which is 4.1-4.3g / cm 3 , which can maintain good high temperature performance in the high temperature range of 600-900℃. As a result, the alloy has become the best iterative material for increasing thrust-to-weight ratio, improving fuel efficiency and achieving lightweight in aerospace and vehicle engines. It has been reported that it has been used in PW1100G-JM aircraft engines.

[0003] TiAl alloy has four typical microstructures, Near gamma (NG), Duplex (DP), Nearly full lamellar (NL) and Full lamellar (FL). Among them, the full lamellar structure has higher high temperature strength, creep resistance and fracture toughness than other structures, and is an ideal structure for TiAl alloy applications. According to the Hall-etch relationship, the gradual reduction of grains has an improving effect on the strength and plasticity of the alloy. Therefore, the fine and uniform full lamellar structure is the best structure for the application of this type of alloy, so many researchers are committed to the study of fine and uniform full lamellar structure.

[0004] "Liu Liangliang, Liu Dong, Liu Renci, Cui Yuyou, Yang Rui. Effect of heat treatment on microstructure and tensile properties of TiAl alloy extruded square bars. Rare Metal Materials and Engineering, 2017, 46: 95-98" The effect of heat treatment process after deformation on the microstructure of extruded Ti-47Al-2Cr-2Nb-0.15B bars was studied. It was found that when heat treated in the temperature range of 1150-1350℃, a transformation from near-γ structure → dual-state structure → lamellar structure occurred. When heat treated at the eutectoid point temperature, the residual lamellar structure produced by extrusion will limit the growth of equiaxed γ phase, so that the microstructure of the alloy retains the morphology during deformation. Therefore, the homogenization treatment of extruded TiAl alloy should be aimed at eliminating the residual lamellar structure, and different microstructure morphologies should be obtained through heat treatment process, and reasonable optimization should be carried out on this basis.

[0005] "Bolz S, Oehring M, Lindemann J, et al. Microstructure and mechanical properties of a forged β-solidifyingγTiAl alloy in different heat treatment conditions. Intermetallics, 2015, 58: 71-83." Based on the attempt of heat treatment experiment on TNM alloy, a two-stage heat treatment process of high temperature solid solution and low temperature aging was proposed to obtain a near-lamellar structure, but its purpose was also to eliminate the residual lamellar after deformation.

[0006] The present invention designs a heat treatment system to solve the problem of uneven structure of deformed materials through step-by-step heat treatment, obtains fine and uniform full-lamellar structure, and the size of the lamella cluster can be controlled within 100 μm. The present invention avoids using a process with an excessively high cooling rate (such as quenching), and can provide a reasonable process for homogenization heat treatment of large-size deformed TiAl alloys. Summary of the invention

[0007] The purpose of the present invention is to avoid the shortcomings of the prior art and provide a three-stage heat treatment process for improving the problem of disordered and uneven microstructure of deformed TiAl alloy, obtaining a TiAl alloy billet with uniform structure, improving the comprehensive performance of the TiAl alloy, and adapting to subsequent thermal / mechanical processing to homogenize the structure of the TiAl alloy after deformation.

[0008] To achieve the above object, the technical solution adopted by the present invention includes the following steps:

[0009] Step 1, taking the TiAl alloy blank after thermal deformation as a TiAl alloy heat treatment sample, and the insulation medium is air;

[0010] Step 2: Place the heat treatment sample in a heat treatment furnace and heat it to the middle and upper temperature zone of the (α+γ) dual phase region. After keeping it warm for a period of time, quickly transfer it to another heat treatment furnace, and the transfer time should be as short as possible.

[0011] Step 3: After the temperature of the heat treatment furnace is set to above the γ solution temperature and kept for a period of time, it is quickly transferred to another heat treatment furnace with the transfer time as short as possible;

[0012] Step 4: The temperature of the heat treatment furnace is set to near the eutectic transformation temperature and then cooled at different cooling rates (furnace cooling / air cooling / controlled cooling) to obtain a uniform full-lamellar structure or a nearly full-lamellar structure, and the size of the lamellar cluster can be controlled within 100 μm.

[0013] Compared with the original microstructure, the first step of heat treatment can effectively eliminate the residual lamellar and twisted coarse lamellar in the original deformed structure, effectively eliminate the internal stress caused by deformation, and use processes such as recrystallization to spheroidize the deformed γ grains to a certain extent, and obtain a uniform dual-state structure. The second step of heat treatment uses a short-term heat treatment in the α single-phase region to obtain uniform α grains. The size of the α grains is controlled by the time of this step. The third step of heat treatment, T eu Keep the temperature close to the specified value, and control the α→γ phase transition process during cooling to reasonably control the spacing of α2 / γ lamellar structures as required.

[0014] Furthermore, in the step 1, the atomic percentage of the elements of the TiAl alloy deformed billet is: Ti-(40-45)Al-XY, wherein the X element is composed of one or more of the β-phase stabilizing elements Cr, Mo, Nb, V, and W, and the Y element is composed of C, B, Si, N, and Re elements. The total atomic content of the X element does not exceed 10%, the total atomic content of the Y element does not exceed 1%, and the rest are impurity elements.

[0015] Furthermore, in the step 1, the deformation amount of the deformed TiAl alloy is ≥50% and the structure is broken, and the microstructure consists of twisted and residual α2 / γ lamellae, equiaxed γ grains and part of α2, β o Grain composition.

[0016] Furthermore, in step 2, the TiAl alloy heat treatment sample is placed in a heat treatment furnace and heated to the middle and upper temperature zone of the (α+γ) dual phase region, specifically 20 to 60°C below the γ solution temperature (T γsolve -(20~60℃)), the holding time is 7~24h, and then it is quickly transferred to another heat treatment furnace. The transfer time should be as short as possible and the converter time should be controlled within 20s.

[0017] Furthermore, in step 3, the TiAl alloy heat treatment sample is quickly transferred to a furnace temperature of 0 to 50° C. above the γ solution temperature (T γsolve +(0~50℃)) heat treatment furnace, keep warm for 5~60min, and transfer quickly after the time is up, the transfer time is the same as above.

[0018] Furthermore, in step 4, the TiAl alloy heat treatment sample is quickly transferred to a furnace with a temperature of 0 to 50° C. (T eu ±(0~50℃)), keep warm for 0~60min, cool at different cooling rates (furnace cooling / air cooling / controlled cooling), and a full-layer or nearly full-layer structure with uniform structure and controllable layer distance can be obtained.

[0019] Furthermore, the heat treatment furnace in steps 2 to 4 is a common heat treatment furnace with air medium.

[0020] Furthermore, in the step 2, the sample is heated up along with the furnace, and timing starts after reaching the set temperature.

[0021] Furthermore, in the steps three and four, the heat treatment sample is placed in the uniform temperature zone of the heat treatment furnace, and the timing is started after the temperature of the heat treatment furnace returns to the set temperature.

[0022] The invention provides a method for homogenizing and regulating the structure of a deformed TiAl alloy material. The method can achieve the purpose of homogenizing and regulating the structure of deformed materials of different sizes through a simple process.

[0023] The beneficial effects of the present invention are as follows: The present invention can obtain a full-lamellar or nearly full-lamellar structure with uniform distribution of the structure, controllable lamellar cluster size and lamellar spacing through the homogenization control method of TiAl deformed alloy, and heat preservation in the middle and upper temperature zones of the α+γ dual-phase region to homogenize the alloy structure and obtain a dual-state structure. Then, a short-term heat treatment is performed in the α single-phase region to control the lamellar cluster size by controlling the treatment time. Then, the eutectoid transformation temperature of 0 to 50°C (T eu ±(0~50℃)) insulation and cooling are used to control the size of the interlamellar spacing, and finally a uniform full-lamellar structure or nearly full-lamellar structure is obtained. The whole heat treatment adopts a step-by-step process to avoid microcracks caused by extremely rapid cooling. The process flow of this method is simple and the cycle is short, which provides an ideal microstructure for the smooth implementation of subsequent thermal / mechanical processing of TiAl alloys. At the same time, the equipment required for the process is simple, easy to operate, and low in cost, and it can be applied to the homogenization of the structure of deformed billets of various sizes. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The microstructure of the extruded alloy Ti44.5Al4Nb0.5Mo0.1B is mainly composed of twisted and residual α2 / γ lamellae, equiaxed γ grains and some α2, β o Grain composition.

[0025] Figure 2 This is the structure obtained after the extruded deformed alloy Ti44.5Al4Nb0.5Mo0.1B undergoes the first step of the three-step heat treatment in Example 1.

[0026] Figure 3 This is the structure obtained after the extruded deformed alloy Ti44.5Al4Nb0.5Mo0.1B is subjected to the three-step heat treatment in Example 1.

[0027] Figure 4This is the structure obtained after the extruded deformed alloy Ti44.5Al4Nb0.5Mo0.1B is subjected to the three-step heat treatment in Example 2.

[0028] Figure 5 This is the structure obtained after the extruded deformed alloy Ti44.5Al4Nb0.5Mo0.1B is subjected to the three-step heat treatment in Example 3. Specific implementation plan

[0029] The technical solution of the present invention is further described below in conjunction with embodiments.

[0030] Example 1

[0031] This embodiment takes the alloy Ti44.5Al4Nb0.5Mo0.1B as an example, and performs deformation and heat treatment on the alloy. The deformation method adopts conventional jacket extrusion, and the cumulative extrusion ratio is 14. The original structure after deformation is as follows Figure 1 As shown in Figure 1, it is mainly composed of a mixed structure with residual coarsened lamellae, equiaxed γ grains and α grains. The eutectoid transformation temperature T eu =1134℃, γ solid solution temperature T γsolve =1280℃.

[0032] Step 1: Use electric spark wire cutting to obtain square block samples of 15*15 mm and perform heat treatment. The high-temperature furnace model is SX-G12163 and the low-temperature furnace model is ZK-9XY-14TP;

[0033] Step 2: Place the heat-treated sample in a furnace, heat the furnace to 1240°C, and keep the temperature for 24 hours to obtain a uniform structure. Figure 2 shown.

[0034] Step 3: The sample is transferred to a 1290°C high temperature furnace, which takes about 15 seconds.

[0035] Step 4: Heat the furnace at 1290°C for 5 minutes.

[0036] Step 5: The sample is transferred to a 1050°C high temperature furnace, and the transfer takes about 15 seconds.

[0037] Step 6: Keep the temperature in a high temperature furnace at 1100°C for 5 minutes and then cool in air. Figure 3 The lamellae shown have a uniform, nearly fully lamellae organization, with an average lamellae cluster size of 60 μm.

[0038] Example 2

[0039] This embodiment takes the alloy Ti44.5Al4Nb0.5Mo0.1B as an example, and performs deformation and heat treatment on the alloy. The deformation method adopts conventional jacket extrusion, and the cumulative extrusion ratio is 14. The original structure after deformation is as follows Figure 1 As shown in Figure 1, it is mainly composed of a mixed structure with residual coarsening and kinked lamellae, equiaxed γ grains and βo grains. The eutectoid transformation temperature T eu =1134℃, γ phase solid solution temperature T γsolv =1280℃.

[0040] Step 1: Use electric spark wire cutting to obtain square block samples of 15*15 mm and perform heat treatment. The high-temperature furnace model is SX-G12163 and the low-temperature furnace model is ZK-9XY-14TP;

[0041] Step 2: Place the heat-treated sample into a furnace, heat the furnace to 1235°C, keep the temperature for 17 hours, and then quickly convert the furnace for 15 seconds.

[0042] Step 3: The sample is transferred to a 1295°C high temperature furnace, which takes about 15 seconds.

[0043] Step 4: Heat in a high temperature furnace at 1295°C for 35 minutes.

[0044] Step 5: The sample is transferred to a high-temperature furnace at 1100°C, and the transfer takes about 15 seconds.

[0045] Step 6: Keep the temperature in a high temperature furnace at 1100°C for 5 minutes and then cool in air. Figure 5 The lamellae shown have uniform full-lamellar organization, with an average lamellae cluster size of 100 μm and small interlamellar spacing.

[0046] Example 3

[0047] This embodiment takes the alloy Ti44.5Al4Nb0.5Mo0.1B as an example, and performs deformation and heat treatment on the alloy. The deformation method adopts conventional jacket extrusion, and the cumulative extrusion ratio is 14. The original structure after deformation is as follows Figure 1 As shown in Figure 1, it is mainly composed of a mixed structure with residual coarsening and kinked lamellae, equiaxed γ grains and βo grains. The eutectoid transformation temperature T eu =1134℃, γ solid solution temperature T γsolv =1280℃.

[0048] Step 1: Use electric spark wire cutting to obtain square block samples of 15*15mm for heat treatment. The high-temperature furnace model is SX-G12163 and the low-temperature furnace model is ZK-9XY-14TP.

[0049] Step 2: Place the heat-treated sample into a furnace, heat the furnace to 1235°C, keep the temperature for 15 hours, and then quickly convert the furnace for 15 seconds.

[0050] Step 3: The sample is transferred to a 1285°C high temperature furnace, which takes about 15 seconds.

[0051] Step 4: Keep the temperature in a high temperature furnace at 1295°C for 20 minutes.

[0052] Step 5: The sample is transferred to a high-temperature furnace at 1150°C, and the transfer takes about 15 seconds.

[0053] Step 6: Keep the temperature in a high temperature furnace at 1150°C for 5 minutes and then cool the furnace. Figure 5 The lamellae shown have uniform full-lamellar organization, with an average lamellae cluster size of 100 μm and large interlamellar spacing.

Claims

1. A method for homogenizing a deformed TiAl alloy structure, characterized in that The following steps are involved: Step 1: The TiAl alloy blank after thermoplastic deformation is used as a TiAl alloy heat treatment sample, and the cross-sectional shape of the TiAl alloy heat treatment sample is not limited; Step 2: placing the TiAl alloy heat treatment sample into a box-type heat treatment furnace, and heating it to the middle and upper temperature zone of the α+γ dual phase region; Step 3: quickly transfer the TiAl alloy heat treatment sample obtained in step 2 into a heat treatment furnace for heat preservation; the temperature of the heat treatment furnace is set to 0 to 50° C. above the γ solution temperature; Step 4, the TiAl alloy heat-treated sample obtained in step 3 is quickly transferred into a heat treatment furnace for heat preservation, the temperature of the heat treatment furnace is set to 0-50° C. near the eutectoid transformation temperature, and a full-lamellar or nearly full-lamellar structure with controllable interlamellar spacing and uniform organization is obtained by cooling at different cooling rates; The atomic percentage of the elements in the TiAl alloy composition is: Ti-(40-45)Al-XY, wherein the X element is composed of one or more of the β-phase stabilizing elements Cr, Mo, Nb, V, and W, and the Y element is composed of C, B, Si, N, and Re. The total atomic content of the X element does not exceed 10%, the total atomic content of the Y element does not exceed 1%, and the rest are impurity elements; The thermoplastic deformation of the deformed material is ≥50% and the structure is broken; the microstructure is composed of twisted and residual α2 / γ lamellae, equiaxed γ grains and part of α2, β o Grain composition.

2. A method for controlling the homogenization of deformed TiAl alloy structure according to claim 1, characterized in that: In the step 2, the furnace temperature during the heat treatment of the TiAl alloy is in the middle and upper temperature zone of the α+γ dual phase region, that is, 20 to 60° C. below the γ solid solution temperature (T γsolve -(20~60℃)), the temperature setting needs to refer to the equilibrium phase diagram or quenching test results, the holding time is 7~24h, the furnace is quickly converted, and the transfer time is 0~20s.

3. A method for controlling the homogenization of deformed TiAl alloy structure according to claim 1, characterized in that: In step 3, the furnace temperature during the heat treatment of the TiAl alloy is 0 to 50°C above the γ solution temperature (T γsolve +(0~50℃)), the holding time is 5~60min, the furnace is quickly converted, and the transfer time is 0~20s.

4. A method for controlling the homogenization of deformed TiAl alloy structure according to claim 1, characterized in that: In step 4, the furnace temperature during the heat treatment of the TiAl alloy is around the eutectoid transformation temperature (T eu ±(0~50℃)), the holding time is 0~60min, the cooling method can be adjusted according to needs, and the size of the flake group can be controlled within 100μm.

5. A method for controlling the homogenization of deformed TiAl alloy structure according to claim 1, characterized in that: The heat treatment furnace in steps 2 to 4 is a common heat treatment furnace with air medium.

6. A method for controlling the homogenization of deformed TiAl alloy structure according to claim 1, characterized in that: In the step 2, the sample is heated up along with the furnace, and timing starts after reaching the set temperature.

7. A method for controlling the homogenization of deformed TiAl alloy structure as claimed in claim 1, characterized in that: In the steps three and four, the heat treatment sample is placed in the uniform temperature zone of the heat treatment furnace, and the timing starts after the temperature of the heat treatment furnace returns to the set temperature.

8. A method for controlling the homogenization of deformed TiAl alloy structure as claimed in claim 1, characterized in that: In step 4, the cooling method can be selected from furnace cooling, air cooling or temperature-controlled cooling according to the final organizational requirements.

Citation Information

Patent Citations

  • Process for obtaining fine fully lamellar structure from high-niobium TiAl alloy

    CN114196898A